Digital narrative conventions in heritage trail mobile apps. Issue 1 (3rd April 2019) - Basaraba, Nicole; Conlan, Owen; Edmond, Jennifer; Arnds, Peter
ABSTRACT: Galleries, libraries, archives and museums (GLAMs) are increasingly using digital technologies for storytelling and creating mobile applications (apps) for cultural heritage content, but how apps are used in practice to communicate information to users has not been widely studied. A team of people from a heritage organisation, a university, and mobile app development group plan to create a bespoke heritage trail app for Ireland, but to date design conventions/recommendations for this genre are lacking. This article applies a systematic approach to digital narrative content analysis to better understand how apps are being used specifically for heritage trails with the aim of identifying what the common features are, which modalities and narrative techniques are used. The selected corpus included 55 apps downloaded from the Google Play Store. The results of this content analysis—based on the App Walkthrough Method (Light, B., Burgess, J., & Duguay, S. (2018). The walkthrough method: An approach to the study of apps. New Media & Society, 20 (3), 881–900)—show that there is a gap between academic research themes/trends and how digital narrative is actually being communicated in the current market, and it aims to inform the future development of heritage trail apps by including a list of design and content features common to this genre.